Prehistoric Chaco Canyon, New Mexico: Importation of meat and maize. (November 2019) - Benson, Larry V.; Grimstead, Deanna N.; Stein, John R.; Roth, David A.; Plowman, Terry I.
Abstract: In a recent paper, Benson and Grimstead (2019) determined that only minimal amounts of maize could have been grown in Chaco Canyon due to its aridity, short growing season, and frequent summer flooding of the valley floor. In this paper it is shown that deer and rabbit densities within semiarid regions such as the Canyon are such that 2300 Canyon residents would eliminate essentially all small and large mammals within a year. This implies that food (meat and maize) must have been imported from one or more outlying areas to feed the Canyon's residential population. This would have entailed ~18, 000 annual trips to the Canyon by porters carrying 45 kg. Although some Sr-isotope data on archaeofauna and maize recovered from Chaco match Sr-isotope values of soil extracts collected in the Canyon (Benson, 2010, 2012; Grimstead et al., 2016), the Canyon's low mammal densities and poor agricultural potential led to a search for other food-source areas with matching Sr-isotope ranges. New isotopic data indicated that the Chuska mountain region appears to be a primary source of these materials. However, there are also a number of other high-elevation relatively wet regions on the periphery of the San Juan Basin with soils having Sr-isotope values that match Chaco Canyon archaeofaunal values, especially values obtained on deer. Highlights: Low mammal densities in Chaco could not supply enough meat to feed 2300 residents. 87 Sr/ 86 Sr data suggest archaeofauna came mainly but not only from the Chuskas. In order to feed 2300 Chaco residents, porters carrying 44 kg must make 18, 000 annual trips.